(untitled) (SAARC Journal of Agriculture, 2014)
Fish ball in curry (FBC) was prepared following standard recipe. Prepared FBC was packed in standup pouches and stored at 0 to -2°C. The organoleptic scores for overall acceptability of the FBC were slightly decreased within the storage period (12 days). The pH decreased from 6.38 to 6.07, while peroxide value increased from 2.27 to 9.47. The total volatile base-nitrogen (TVB-N) increased from 5.04 to 17.64. The total plate count increased from an initial value of 1.8 x 102 to 2.4 x 104 cfu g-1 during chilled storage. The Staphylcoccus aureus, Escherichia coli and Salmonella sp. were not detected throughout the study period. It was observed that the products stored at 0 to -2°C were acceptable organoleptically, and stable biochemically and microbiologically up to 9 days. DOI: http://dx.doi.org/10.3329/sja.v11i1.18373 SAARC J. Agri., 11(1): 35-43 (2013)